Blue Ocean Strategy in Healthy Bakeries in Bali - Putri, Dewa Ayu Iva Kayana (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study aims to analyze the implementation of the Blue Ocean Strategy in healthy bakeries in Bali in creating new market spaces and sustainable competitive advantages. The research employed a qualitative approach using a case study method at Oka’s Bakery & Cafe, Finnfit Bakery, and Bali Buda. The findings reveal that the three bakeries successfully established new market spaces grounded in the healthy lifestyle trend through value innovation, product differentiation, and enhanced customer experience. Finnfit Bakery demonstrated the strongest strategy in developing a niche market based on the concept of a fitness-oriented bakery, while Bali Buda excelled in emotional branding and sustainability practices. Oka’s Bakery illustrated a transformation process from a conventional bakery into a health-oriented bakery business. The study further indicates that value innovation occurs not only at the product level but also within the dimensions of consumption experience and the lifestyle meanings offered to customers. The competitive advantages possessed by healthy bakeries in Bali are characterized as valuable, rare, inimitable, and non-substitutable.